1972
DOI: 10.1002/hlca.19720550522
|View full text |Cite
|
Sign up to set email alerts
|

Notiz über das Vorkommen von 4′,5‐Dihydroxy‐3,3′,6,7‐tetramethoxyflavon (Chrysosplenetin) in Plectranthus marrubioides HOCHST (Labiatae)

Abstract: Chrysosplenetin (4′, 5‐dihydroxy‐3,3′, 6,7‐tetramethoxyflavon) has been isolated from the leaves of Plectranthus marrubioides HOCHST (Labiatae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Flavonoids seem to be rare in Plectranthus . Only two flavonoids were identified, 4',7-dimethoxy-5,6-dihydroxyflavone ( M10 ) from P. ambiguus [ 33 ] and chrysosplenetin ( M11 ) from P. marruboides [ 34 ]. From P. mollis (= P. incanus ), Mahmoud et al reported the isolation of vernolic and cyclopropenoid fatty acids [ 35 ].…”
Section: Miscellaneous Constituentsmentioning
confidence: 99%
“…Flavonoids seem to be rare in Plectranthus . Only two flavonoids were identified, 4',7-dimethoxy-5,6-dihydroxyflavone ( M10 ) from P. ambiguus [ 33 ] and chrysosplenetin ( M11 ) from P. marruboides [ 34 ]. From P. mollis (= P. incanus ), Mahmoud et al reported the isolation of vernolic and cyclopropenoid fatty acids [ 35 ].…”
Section: Miscellaneous Constituentsmentioning
confidence: 99%
“…Furthermore, extensive phytochemical investigation on different species of Plectranthus revealed that diterpenoids are the main chemical constituents of the genus Plectranthus besides the essential oils (12,2). Other constituents found are triterpenoids (13,), steroids (14,), phenolics (15), flavonoids (16,17) and fatty acids (2,4). In Saudi Arabia, genus Plectranthus is comprised of nine naturally growing aromatic flowering plant species, which are often locally used in traditional medicinal practices, as ornamental and perfumery products (18).…”
Section: Introductionmentioning
confidence: 99%